Identifikasi Temuan Arca di Karangnunggal, Tasikmalaya: Identification of the Sculptures Findings in Karangnunggal, Tasikmalaya - Nanang Saptono; Endang Widyastuti (Kemendikbud, 2021)
Sculptures are archaeological relic that are frequently found. Sculptures from the Hindu-Buddhist period often serves as a medium for worshipping. The characters depicted in the sculpture can be of gods and their pantheons, some are in the form of kings who are depicted as gods. In the area of Karangnunggal, Tasikmalaya, sculpture made of stone were found on a former plantation land that was used during the Dutch era. This article aims to provide an overview of the character that are depicted in the sculpture, the origin style of the creation, and when the sculpture was created. The method used in this research is descriptive research with a comparative approach. Based on its attributes, the Karangnunggal sculpture considered as a sculpture of embodiment. The figure that depicted was Dewi Parwati in Majapahit style. Based on the context of the findings, this sculpture indicates as an art item created at present time.